Pemberdayaan UMKM Desa Melalui Pelatihan Partisipatif Berbasis Inovasi Produk: Studi Kasus Keripik Pisang Lumer di Pulau Kedundung - Piawi, Kiprah; Nurlita, Dela; Nazira, Arni; Rahayu, Vania Gitta; Anjli (CV Najmi Edu Creative, 2025)
The Indonesian government is increasingly promoting innovative local food products as alternative drivers of economic growth and food diversification. In Pulau Kedundung Village, an abundant banana harvest remains underutilized due to a lack of processing innovation. This community service program aimed to empower local micro, small, and medium enterprises (MSMEs) through participatory training focused on transforming bananas into melted banana chips—a novel, value-added product. The June 12, 2025, training involved 10 local participants, emphasizing practical product innovation, including raw material processing, packaging, and basic marketing strategies. Pre- and post-training assessments revealed a 52% improvement in participants’ knowledge of product innovation. Furthermore, a 72% increase in socio-economic impact was reported, marked by heightened readiness to start or expand businesses and the establishment of two new home-based enterprises. These outcomes suggest that participatory, innovation-based training effectively strengthens rural MSME capacity and fosters sustainable local economic development. This case study highlights the critical role of grassroots innovation and entrepreneurship education in unlocking rural economic potential.